Local Editing of Procedural Models. (7th June 2019) - Lipp, M.; Specht, M.; Lau, C.; Wonka, P.; Müller, P.
Abstract: Procedural modeling is used across many industries for rapid 3D content creation. However, professional procedural tools often lack artistic control, requiring manual edits on baked results, diminishing the advantages of a procedural modeling pipeline. Previous approaches to enable local artistic control require special annotations of the procedural system and manual exploration of potential edit locations. Therefore, we propose a novel approach to discover meaningful and non‐redundant good edit locations (GELs). We introduce a bottom‐up algorithm for finding GELs directly from the attributes in procedural models, without special annotations. To make attribute edits at GELs persistent, we analyze their local spatial context and construct a meta‐locator to uniquely specify their structure. Meta‐locators are calculated independently per attribute, making them robust against changes in the procedural system. Functions on meta‐locators enable intuitive and robust multi‐selections. Finally, we introduce an algorithm to transfer meta‐locators to a different procedural model. We show that our approach greatly simplifies the exploration of the local edit space, and we demonstrate its usefulness in a user study and multiple real‐world examples.